Hubungan Kualitas Tidur dengan Imunitas Tubuh pada Pekerja Shift Malam - Indriani Indriani; Sohibul Hamdi (Lembaga Penelitian dan Pendidikan, 2025)
Night shift workers are at a high risk of experiencing sleep disturbances, which can negatively affect the immune system. This study aims to analyze the relationship between sleep quality and immune function among night shift workers. A cross-sectional research design was employed with a total sample of 120 night shift workers in a manufacturing company. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), while immune status was assessed through leukocyte count and immunoglobulin G (IgG) levels. The results revealed that 68.3% of respondents had poor sleep quality, and 54.2% showed decreased immunity. Spearman correlation analysis indicated a significant relationship between sleep quality and immune function (p < 0.05), with workers who reported poor sleep quality tending to have lower immune function compared to those with good sleep quality. These findings emphasize the importance of sleep management and occupational health interventions to minimize the adverse effects of shift work on the immune system. The study recommends the implementation of sleep management programs and health promotion initiatives for night shift workers to maintain immune function and reduce vulnerability to diseases.